Risk management and bank performance: a case study of First Atlantic Merchant Bank Ghana Limited (FAMBL) - Opoku-Adarkwa, Ruth (2012)
A Thesis submitted to the Institute of Distant Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Business Administration, June, 2011